Molecular detection of metallo-β-lactamase genes in carbapenem-resistant isolates of Pseudomonas aeruginosa recovered from patients in Al-Diwaniyah province, Iraq - Hussein Al-abedi, Khawlah Jabbar; Abd Al-Mayahi, FiarsSrhan (Al-Qadisiyah Journal of Pure Science, 2019)
Introduction: The World Health Organization(WHO) has rated Carbapenems Resistant Pseudomonas aeruginosafrom top priority pathogens to research and develop new antibiotics. Objectives: The current work intended to detect the presence of the metallo-β-lactamase genes in Pseudomonasaeruginosa isolates cultivated from some healthcare centers in Al-Diwaniyah City, Iraq. Materials and methods: After induction of specific traditional cultivation and identification methods for 630 samples (244 burn swabs, 163 sputa, 115 urine samples, and 108 ear swabs), a monoplex polymerase chain reaction (MPCR) method aiming at 8 metallo-β-lactamases (MBLs) genes was followed. Partial-gene sequencing of the MBLs was also performed to understand some of the evolution history of those isolates. Results: The P. aeruginosa was identified in 100 isolates. MBL-related MPCR results showed the presence of blaVIM, blaSPM, blaGIM, blaNDM, blaAIM,blaSIM, and blaDIM genes in 16 (66.6%), and 14 (14.3%), 13 (54.1%), 1 (36.5%), 9 (37.5%), 8 (33.3%), 2 (8.3%), respectively, of the isolates. No detection of the blaIMP was observed. The phylogenic study demonstrated high matching rates, 99%, with global strains from the NCBI-related database. Conclusion: To the best of our awareness, the current work is the first in Iraq identifying metallo-β-lactamase genes in Pseudomonasaeruginosa isolates.